Design and Analysis of a Shock Absorber with a Variable Moment of Inertia Flywheel for Passive Vehicle Suspension - Xu, Tongyi (Université d'Ottawa / University of Ottawa, 2013)
Conventional vehicle suspensions consist of a spring and a damper, while mass is rarely used. A mass, if properly used, can also create a damping-like effect. However, a mass has only one terminal which makes it difficult to be incorporated into a suspension. In order to use a mass to achieve the damping-like effect, a two-terminal mass (TTM) has to be designed. However, most of the reported TTMs are of fixed moment of inertia (TTM-CMI), which limits the further improvement of the suspension performance and responsiveness to changes in environment and driving conditions. In this study, a TTM-based vibration absorber with variable moment of inertia (TTM-VMI) is proposed. The main component of the proposed TTM absorber contains a hydraulic-driven flywheel with sliders. The moment of inertia changes with the positions of the sliders in response to the driving conditions. The performance of the proposed TTM-VMI absorber has been analyzed via dynamics modeling and simulation and further examined by experiments. The analysis results indicate that the TTM-VMI absorber outperforms the TTM-CMI design in terms of body displacement; and ride comfort, tire grip and suspension deflection for zero and impulse inputs with comparable performance for sinusoidal input.
Keywords: two-terminal mass; variable moment of inertia flywheel; passive vehicle suspension; variable vehicle body mass; ride comfort; tire grip; suspension deflection